Indication and eligibility of glioma patients for awake surgery: A scoping review by a multidisciplinary perspective - Fiore, Giorgio; Abete-Fornara, Giorgia; Forgione, Arianna; Tariciotti, Leonardo; Pluderi, Mauro; Borsa, Stefano; Bana, Cristina; Cogiamanian, Filippo; Vergari, Maurizio; Conte, Valeria; Caroli, Manuela; Locatelli, Marco; et al. (Frontiers in Oncology, 2022)
Background:Awake surgery(AS) permits intraoperative mapping of cognitive and motor functions, allowing neurosurgeons to tailor the resection according to patient functional boundaries thus preserving long-term patient integrity and maximizing extent of resection.Given the increased risks of the awake scenario, the growing importance of AS in surgical practice favored the debate about patient selection concerning both indication and eligibility criteria.Nonetheless, a systematic investigation is lacking in the literature. Objective:To provide a scoping review of the literature concerning indication and eligibility criteria for AS in patients with gliomas to answer the questions:1)“What are the functions mostly tested during AS protocols?” and 2)“When and why should a patient be excluded from AS?”. Materials and Methods:Pertinent studies were retrieved from PubMed, PsycArticles and Cochrane Central Register of Controlled Trials(CENTRAL),published until April 2021 according to the PRISMA Statement Extension for Scoping Reviews.The retrieved abstracts were checked for the following features being clearly stated:1)the population described as being composed of glioma(LGG or HGG) patients; 2)the paper had to declare which cognitive or sensorimotor function was tested, or 2bis)the decisional process of inclusion/exclusion for AS had to be described from at least one of the following perspectives: neurosurgical, neurophysiological, anesthesiologic and psychological/neuropsychological. Results:One hundred and seventy-eight studies stated the functions being tested on 8004 patients.Language is the main indication for AS, even if tasks and stimulation techniques changed over the years.It is followed by monitoring of sensorimotor and visuospatial pathways.This review demonstrated an increasing interest in addressing other superior cognitive functions,such as executive functions and emotions.Forty-five studies on 2645 glioma patients stated the inclusion/exclusion criteria for AS eligibility.Inability to cooperate due to psychological disorder(i.e. anxiety),severe language deficits and other medical conditions(i.e.cardiovascular diseases, obesity, etc.)are widely reported as exclusion criteria for AS.However,a very few papers gave scale exact cut-off.Likewise,age and tumor histology are not standardized parameters for patient selection. Conclusion:Given the broad spectrum of functions that might be safely and effectively monitored via AS,neurosurgeons and their teams should tailor intraoperative testing on patient needs and background as well as on tumor location and features.Whenever the aforementioned exclusion criteria are not fulfilled, AS should be strongly considered for glioma patients.